Pesticide-induced ecological traps and insect pollinator foraging network disruption in apple orchards compared to adjacent graveyard refugia - Muzafar Riyaz; Arfat Nazir; Sabreena Ashraf; Rakesh Kumar Gupta (PLoS ONE, 2026)
Beyond acute toxicity, agricultural pesticide regimes fundamentally restructure insect foraging networks through complex, poorly understood community-level pathways. By comparing eight conventional apple orchards with adjacent pesticide-free graveyard refugia in Shopian, Kashmir, this study documents the ecological cascades triggered by intensive, calendar-based pesticide applications. Orchards supported 68% lower insect abundance and 55% lower species richness than paired graveyards, with hoverflies and solitary bees disproportionately suppressed. Plant-pollinator networks exhibited structural collapse: connectance declined by 46%, nestedness by 46%, and network-level specialization increased by 63% (all p < 0.01), reflecting resource-constrained rather than co-evolutionarily structured communities. Foraging niche breadth contracted significantly across all shared taxa (Paired t-test: t = 5.61, p < 0.001). A chi-square goodness-of-fit test formally demonstrated that April foraging visits were disproportionately concentrated on Brassica campestris relative to its floral availability (76.0% of visits versus 48.0% availability; χ² = 62.88, df = 3, p < 0.001), satisfying the primary analytical criterion for ecological trap identification: this species preferentially attracted over 70% of non- Malus foraging visits during peak neurotoxic insecticide application, in the complete absence of uncontaminated floral alternatives. A parallel trap effect persisted through May–June (χ² = 31.65, df = 3, p < 0.001), extending exposure risk across the season’s most biologically active phase. Functional homogenization followed, with long-tongued insects declining by 78% and functional richness by 62%, driven by direct toxicity and herbicide-mediated elimination of deep-corolla floral resources. These findings elucidate a mechanistic cascade from phenologically triggered trap formation through network collapse to functional homogenization. Conservation strategies must prioritize permanent pesticide-free refugia and temporally explicit restrictions on bee-toxic insecticide application throughout the April–June risk window.